Sistem Informasi Kegiatan Kelompok Tani Di UPT HPT Dan Keswan Praya Timur - Rizky, Muhammad Alfa; Sugiartawan, Putu (INFOTEKS (Information Technology, Computer and Sciences), 2022)
The Central Lombok Agriculture Service is a regional institution that represents the organizers of state affairs under the jurisdiction of the Central Lombok region. Farmer groups in East Praya sub-district, the information process is still manual so something that functions is needed to register farmer groups. With the development of the technological era, it is also developing with the development of network-based technology, which can facilitate the data collection process to provide information. This of course will help rural groups manage and manage organizational strategies to manage the influence of rural groups online. This research resulted in a Farmer Group application designed with features that can be used by administrators and members. Each member has an account to login. Login can be done by entering the credentials by entering the username and password. The development method is usability and web design, the Unified Modeling Language (UML) approach is used in system design, the black box test method is used in software testing which focuses on the input and output functionality of the application. . With the success of the tests carried out, this information system is expected to help rural groups in Central Lombok to work effectively and efficiently.